Smart Mirror Navigation And Personalization Determine Consumer Purchase Intention In Beauty Retail: Navigasi Dan Personalisasi Cermin Pintar Menentukan Niat Beli Konsumen Ritel Kecantikan - Charmela Audria Mumtadz; Tsailasa Fathia; Yolanda Masnita; Husna Leila Yusran (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The integration of augmented reality into digital marketing transforms the modern consumer shopping experience into an interactive and personalized journey. Specific Background Within the beauty retail sector, businesses increasingly adopt smart mirrors to allow consumers to virtually evaluate products through real-time simulations. Knowledge Gap Despite rapid technological growth, previous studies present inconsistent findings regarding user satisfaction and predominantly ignore the critical roles of system navigation and interface personalization. Aims This quantitative study investigates how perceived ease of use, perceived usefulness, personalization, and navigation dictate user satisfaction and subsequent purchase intention for smart mirrors. Results Structural equation modeling of 220 first-time users demonstrates that all examined technological factors positively determine user satisfaction, with system navigation acting as the most dominant predictor. Consequently, this high user satisfaction strongly translates into future purchase intention. Novelty By substituting traditional aesthetic appeal metrics with personalization variables, this research uniquely validates the Technology Acceptance Model within customized digital beauty storefronts. Implications Commercial managers must prioritize intuitive menu designs, logical structures, and responsive search features to maximize navigational experiences and stimulate final transactions in modern retail environments. Highlights Intuitive system navigation emerges as the most dominant predictor of user satisfaction. Perceived usefulness and virtual personalization positively dictate interactive shopping experiences. Positive interface satisfaction strongly translates into future consumer transaction commitments. Keywords Smart Mirror; Technology Acceptance Model; User Satisfaction; System Navigation; Purchase Intention